(untitled) (Costos y Gestión, 2021)
While there is not either cure or effective treatment against COVID-19, vaccines arise as only viable option for the world to come back to “normalcy”. Process of research & development, manufacturing and distribution of COVID-19 vaccine is highly complex. More than 150 vaccine candidates are now being developed through different and indeed revolutionary technologies for having vaccines available by the end of 2020 or early 2021. Objective of this paper is to present a holistic assessment of management, costs and pricing for the COVID-19 vaccine process, studying its whole value chain, including R&D, manufacturing, marketing and distribution, but focusing on costing techniques and methodologies used by companies, always based on their manufacturing models and technologies. Our goal is to make contributions that could be useful for companies and governments on three main aspects: unit cost calculation introducing life-cycle costing approach, effective pricing decisions by pharmaceutical companies and efficient purchasing models implementation by governments. Scientific and technological challenge is huge. From management perspective, decision making process and excellence in execution are key; demand for a collaborative and coordinated actions by all stakeholders is vital to reach the goal of having an effective and safe vaccine that is widely accessed by everybody.